Lecturer’s Perceptions On How Self-Study At English Proficiency Class Should Be Implemented - Ie Anisa; Ririn Ovilia (Journal of English Language Teaching, 2023)
The purpose of this study is to find out the lecturer’s perception on how self-study in English Proficiency class at English Department should be ideally Implemented. This research uses descriptive research with a quantitative approach. This survey study involved ten lecturers teaching English Proficiency class at English Department of Universitas Negeri Padang are chosen using convenience sampling method. Questionnaire consisting 30 items followed by four scales was distributed to the lecturers to collected the data. The results of this study show; The implementation of self-study in English Proficiency classes is considered ideal because it is supported by the required learning media and good assessment. In addition, in relation to lecturers' perceptions of the use of technology in conducting self-study, almost all lecturers strongly agreed that technology can help the self-study because with technology students are easier to access materials. In conclusion, the lecturers have very positive perception on how self-study in English Proficiency class at English Department should be ideally Implemented.